This preview shows page 1. Sign up to view the full content.
13.39:
Using the same procedure used to obtain Eq. (13.29), the potential may be
expressed as
].
)
1
(
2
)
1
[(
6
0
12
0
0


+

+
=
R
x
R
x
U
U
Note that at
.
,
0
0
U
U
R
r

=
=
Using the appropriate forms of the binomial theorem for


0
R
x
<< 1,
(
29
(
29 (
29
(
29
(
29
(
29 (
29
(
29


+




+

≈
2
0
0
2
0
0
0
2
7
6
6
1
2
2
13
12
12
1
R
x
R
x
R
x
R
x
U
U
+

=
2
2
0
0
36
1
x
R
U
This is the end of the preview. Sign up
to
access the rest of the document.